Validity and reliability of wheelchair sitting posture measures using Coach's Eye in abled subjects. Issue 4 (2nd October 2017) - Alkhateeb, Afnan M.; Forrester, Bonnie J.; Daher, Noha S.; Martin, Bradford D.; Alonazi, Asma A.
ABSTRACT: People in wheelchairs spend a long time in the sitting position and often incur alignment problems resulting in neck and back pain. This study: (1) assessed the validity/reliability of Coach's Eye (CE) smart device application, (2) examined the effect of seat to back support angle adjustments on head, neck, and shoulder posture in the sitting position, and (3) compared changes in cervical rotation at each back support angle. Abled subjects sat in a wheelchair with back support angles positioned at 90°, 100°, and 110°. CE, as well as ImageJ software, was used to analyze three angles: sagittal head angle (SHA), cervical angle (CVA), and shoulder angle (SA). There were highly significant differences for CVA and SA ( p < 0.001) among the three seat to back support angles. Validity of CE was examined by correlating CE with ImageJ scores. CE had high validity for all angles ( r = 0.99, 0.98, 0.99 respectively, p < 0.001). Inter-rater reliability for SHA, CVA, and SA was high (intraclass correlation coefficient [ICC] ranged from 0.95 to 0.99). Head (CVA) and shoulder (SA) alignment was closest to neutral posture with back support angles set at 110° and 90°, respectively.